2021
DOI: 10.1158/0008-5472.can-20-2300
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Expanded from PD-1+ Peripheral Blood Lymphocytes Share More Clones with Paired Tumor-Infiltrating Lymphocytes

Abstract: Both tumor-infiltrating lymphocytes (TIL) and PD-1+ peripheral blood lymphocytes (PBL) are enriched for tumor-reactive clones recognizing known and unknown tumor antigens. However, the relationship between the T-cell receptor-β (TCRβ) repertoires of the TILs and T cells expanded from paired PD-1+ PBLs, and whether T cells expanded from PD-1+ PBLs can be used to treat patients with cancer as TIL substitutes remain unclear. Here, we established a highly efficient protocol to prepare polyclonal T cells from PD-1+… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Particularly, we noticed that the tumor draining lymph node attraction markers CCR7 and SELL (CD62L) are expressed only in aged Tex, suggesting that they are recent migrate-in effector memory cells from draining lymph node (Figure 4e). Hence, in concordance with recent results with single cell TCR clonal tracing and clinical observations 48, 49 , our analysis suggest that peripheral influx of tumor-reactive T cells underly anti-PD1 response. Finally, we identified that cis-regulatory loci of a co-receptor and negative regulator of TGF-beta, CD109 (Figure 4f), and the nicotinic acetylcholine receptor CHRNA1 (Figure 4g), are specifically activated in response-associated Tex cells, suggesting novel targets for future research.…”
Section: Resultssupporting
confidence: 92%
“…Particularly, we noticed that the tumor draining lymph node attraction markers CCR7 and SELL (CD62L) are expressed only in aged Tex, suggesting that they are recent migrate-in effector memory cells from draining lymph node (Figure 4e). Hence, in concordance with recent results with single cell TCR clonal tracing and clinical observations 48, 49 , our analysis suggest that peripheral influx of tumor-reactive T cells underly anti-PD1 response. Finally, we identified that cis-regulatory loci of a co-receptor and negative regulator of TGF-beta, CD109 (Figure 4f), and the nicotinic acetylcholine receptor CHRNA1 (Figure 4g), are specifically activated in response-associated Tex cells, suggesting novel targets for future research.…”
Section: Resultssupporting
confidence: 92%
“…In comparison, patients who did not respond to treatment had a stable TCR repertoire where the most frequent clones before treatment maintained their dominance after therapy. Similarly, several studies have previously reported that response to checkpoint therapy is associated with new clones entering the total CD8 or the activated PD1+CD8 T-cell pool (22,41). Finally, we find that the T cell response in a patient's originally resected tumor (with surgery occurring months to years before receiving immunotherapy) predicts later response to checkpoint therapy, where patients with more CD8 T cells in their tumor exhibit improved responses to therapy.…”
Section: Discussionsupporting
confidence: 80%
“…However, we did not find any correlation between the changes in CD8 + T cell and the prognosis. This may be explained by the fact that PD-1 + T cell represent only a small proportion of overall peripheral blood CD8 + T cell, whereas the proliferative burst of CD8 + T cell after PD-1 blockade was almost exclusively derived from the PD-1 + CD8 + T-cell subset (27,28).…”
Section: Discussionmentioning
confidence: 99%